The performance of PPOdm-CNF Mixed Matrix Membrane for CO2/CH4 separation - Murugiah, P.S. (Universiti Malaysia Pahang, 2018)
Mixed Matrix Membrane (MMM) is one of the most promising candidate among the available gas separation application for CO2/CH4 separation in natural gas industries. However, the fabrication of a defect-free MMM remains a challenge. For this work, a novel MMM was developed by incorporating carbon nanofibers (CNF) at different weight loadings into poly (2, 6-dimethyl-1, 4-pheneylene oxide) (PPOdm) polymer matrix via dry-phase inversion technique. CNF was purified with hydrogen peroxide prior to membrane fabrication. Approximately 178 increment in the CO2 permeability were attained at 3 wt of CNF loading whereas the CO2/CH4 selectivity were increased by 53 compared to pristine PPOdm polymeric membrane. The smooth wall of CNF coupled with its larger pore diameter acted as a pathway and renders high gas permeability values. PPOdm - 3 wt CNF MMM exhibits improved morphology with no significant filler agglomeration on the polymer matrix. The TGA and DSC analysis showed that at 3 wt of CNF loading, the thermal stability of the polymer chains was enhanced in which higher decomposition (Td = 425 °C) and glass transition (Tg =210 °C) temperatures were reported. © Universiti Malaysia Pahang, Malaysia.